Implementasi Kritik Sanad dan Matan Hadis Ali Mustafa Yaqub dalam Validasi Hadis: Ali Mustafa Yaqub's Implementation of Hadith Sanad and Matan Criticism in Hadith Validation - Hamma Aming; Zulfahmi Alwi; Sitti Aisyah (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
Ali Mustafa Yaqub is a charismatic cleric who has an important role in the spread of the Prophet's Hadith in Indonesia. And is a reliable expert, especially in the field of hadith, who has produced many works. Among his monumental works are Hadith Criticism and Problematic Hadiths. This article uses library research, namely in the form of books, notes or reports of related research results. The research approach used is the hadith science approach. With this, a hadith is considered valid in a study if the sanad is continuous, the narrator is fair and dhabit and there is no illah or syadz. As a result, understanding hadith will become easier to gain a more precise, dynamic, accommodating, appreciative, comprehensive and easy to understand understanding for people of all ages. The results of this research are that in validating a hadith, Ali Mustafa Ya'qub used the theory of the rules of hadith validity, as a form of attention or caution in selecting the hadith of the Prophet, in order to avoid forgery of the hadith. And the implication for the study of hadith is the importance of research on sanad and matn to maintain the position of the Prophet's hadith as a source of law and prevent the occurrence of falsification of hadith either among Muslims themselves or from orientalist circles.